Haemato-biochemical indices and immune response of grower pigs fed enzyme supplemented dried cassava peel and maize cob composite meal - Anorue, Daniel Nnadozie (Brazilian Journal of Science, 2024)
This study was carried out to examine the haemato-biochemical and immune response of grower pigs fed enzyme supplemented dried cassava peel and maize cob composite meal (CPMCM). A total of 36 crossbreed male grower pigs (Large white) of about 16 weeks old were randomly distributed into four groups of nine animals per treatment. Each treatment was further divided into three replicates consisting of three pigs in a completely randomized design. Pigs in treatment 1 were fed 0% CPMCM while CPMCM was used to replace maize at 40% (T2), 50% (T3) and 60% in T4. Examination of phyto-constituents in CPMCM showed that it contains alkaloids, tannins, saponins, cyanide, phenols and flavonoids at 20.05 mg/kg-1, 9.06 mg/kg-1, 10.04 mg/kg-1, 15.03 mg/kg-1, 8.92 mg/kg-1 and 14.11 mg/kg-1 respectively. Haematological results revealed that red blood cell, pack cell volume, haemoglobin, mean corpuscular haemoglobin, mean corpuscular volume, mean corpuscular haemoglobin concentration, white blood cell, monocytes and lymphocytes were significantly (p < 0.05) influenced by the treatment except for basophils count (p > 0.05). Total protein, total bilirubin, glucose, creatinine, alkaline phosphatase, alanine transaminase and aspartate transaminase values were significantly different among the treatment (p < 0.05) except for cholesterol and urea levels. It was concluded that all the blood parameters evaluated were within the established range for healthy pigs and dietary replacement of cassava peel and maize cob composite meal (CPMCM) with maize up to 60% pose no deleterious effect on the health of the animals.